POTENTIAL ASSOCIATION OF PRIVATE UNIVERSITY BRANDING EFFOTS WITH PERCEPTIONS AND ATTITUDES OF PROSPECTIVE STUDENTS: A STUDY IN SRI LANKA - Preethi PERERA; Nalin ABEYSEKERA; Dinesh SAMARASINGHE (Management & Marketing)
Branding is a key factor that is receiving attention by the private universities in marketing their educational products. It is evident that the perceptions and attitudes of the prospective students could play a vital role in attracting them by these institutions.This study focuses on the prospective students of private universities in Sri Lanka, and it aims to conceptualize such branding efforts and students’ perceptions & attitudes regarding private universities, and to investigate if there could be any potential associations between them. Responses were gathered via an online survey questionnaire, and the results indicate that there are significant positive relationships between branding efforts and students’ attitudes; students’ perceptions and attitudes; and between branding effort and perceptions. Further, students’ perceptions showed a full mediating effect between branding efforts and students’ perceptions.